Atmospheric deposition of polycyclic aromatic compounds and associated sources in an urban and a rural area of Chongqing, China - Tian, Mi; Yang, FuMo; Chen, SheJun; Wang, HuanBo; Chen, Yang; Zhang, LiuYi; Zhang, LeiMing; Xiang, Li; Qiao, BaoQing (Chemosphere (Oxford), 2017)
Monthly bulk (dry + wet) deposition samples were collected at an urban and a rural site in Chongqing, southwestern China during May 2014 to April 2015 for analyzing the contents of parent polycyclic aromatic hydrocarbons (PPAHs) and three types of substituted PAHs (SPAHs) including oxygenated PAHs (OPAHs), nitrated PAHs (NPAHs) and methyl PAHs (MPAHs). Annual average (±standard deviation) deposition fluxes of ΣPPAHs, ΣOPAHs, and ΣMPAHs were 536 ± 216; 221 ± 118, and 131 ± 41.9 ng/m2/d, respectively, in the urban area, and 347 ± 185, 160 ± 112, and 85.2 ± 32.0 ng/m2/d, respectively in the rural area. Deposition of ΣNPAHs (6.01 ± 3.93 and 3.91 ± 4.84 ng/m2/d) were about two orders of magnitude lower than those of ΣPPAHs. In the urban area, temporal variations of PPAHs and MPAHs fluxes were positively correlated with particle deposition, while the trends of OPAHs and NPAHs were probably controlled by secondary formation. In the rural area, SPAHs and PPAHs deposition fluxes had similar temporal trends but differed from particle deposition. High relative humidity in Chongqing likely played an important role in facilitating the partitioning of OPAHs to atmospheric aerosols and resulting in the relatively high OPAHs level in winter. Principle component analysis identified secondary formation (21.7%) and combustion emission (52.7%) as two important contributors to polycyclic aromatic compounds (PACs) deposition fluxes in urban area. •Atmospheric deposition of PPAHs, NPAHs and OPAHs were measured in Chongqing.•OPAHs occurred in all samples with deposition flux 2 times lower than PPAHs.•Both secondary formation and combustions had impacts on PACs in Chongqing.•High relative humidity may be important for the high OPAHs deposition in winter.